Prečkanja cest preko vodovarstvenih območij - Brenčič, Mihael (Geologija, 2004)
Crossing of drinking water protection zones by roads are very common phenomenon in Slovenia. Described are starting points for protection of drinking water resources implemented with new legislation. In the article emphasize is given on the road and drinking water interaction. This new legislation implements also procedures for new construction impact assessment on protected drinking water resources. Assessments are defined as risk analysis. Some theoretical bases for these procedures are given.
Keywords: ceste; cestni promet; onesnaževanje voda; podzemne vode; Slovenia; Slovenija; vodni viri; vodonosniki; zaščita